Building Sustainable Nonprofit Organizations Through Effective Financial Management - Unzilah Khomairotusshiyama; Khoiriyah Khoiriyah; Musammil Lateh (Business and Applied Management Journal, 2023)
This research aims to analyze financial management practices in building the sustainability of nonprofit organizations. This research is based on financial management strategies that are applied to maintain operational stability, program sustainability and increase stakeholder trust. The research method used is a descriptive qualitative approach with data collection techniques through in-depth interviews, direct observation, and analysis of financial documents over the past three years. The results show that effective financial management includes transparency in reporting, participation in budget planning, consistent internal oversight, and diversification of funding sources, such as collaboration with external partners and optimization of institutional assets. The study results show that the organization’s sustainability is greatly influenced by the management’s commitment to carrying out the principles of accountability and efficiency in using funds. The implications of this study show that a strong financial management capacity is an important foundation for the sustainability of nonprofit organizations. These findings are expected to serve as a practical reference for similar institutions in designing financial systems that are adaptive, professional, and impact-oriented to long-term impact.